The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1080/02670836.2019.1590504
|View full text |Cite
|
Sign up to set email alerts
|

Compressive properties and cracking behaviour of 3D interpenetrating hierarchical Al2O3p/steel composite

Abstract: A hierarchical-architectured Al2O3/40Cr steel composite was fabricated by squeeze casting. In the composite, the Al2O3 particulate-reinforced 40Cr steel matrix composite and pure 40Cr steel formed a 3D interpenetrating composite. The uniaxial compressive properties as well as the cracking behaviour, the strengthening and toughening mechanisms of the composite were investigated and discussed. The compressive strength, fracture strain, and elasticity modulus of the architectured composite are 903.5 MPa, 18.8%, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Obviously, this method is only suitable for research because the drilling process greatly reduces the preparation efficiency. Lu et al [39] prepared templates of plastics containing the needed architecture by 3D printing, then filled them with mixed powders of ceramic and base metal, and finally prepared three-dimensional interpenetrating network composites by pressure infiltration technology. This method can improve the accuracy of the architecture but can only be applied to architectured composites where the soft phase regions and the hard phase regions are It cannot be used for architectured composites where one of the soft phase regions and the hard phase regions are continuous and the other is dispersed.…”
Section: Discussionmentioning
confidence: 99%
“…Obviously, this method is only suitable for research because the drilling process greatly reduces the preparation efficiency. Lu et al [39] prepared templates of plastics containing the needed architecture by 3D printing, then filled them with mixed powders of ceramic and base metal, and finally prepared three-dimensional interpenetrating network composites by pressure infiltration technology. This method can improve the accuracy of the architecture but can only be applied to architectured composites where the soft phase regions and the hard phase regions are It cannot be used for architectured composites where one of the soft phase regions and the hard phase regions are continuous and the other is dispersed.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 10 shows the compression fracture morphology of the honeycomb composite. From the compressive fracture morphology of honeycomb composites, it can be judged that the fracture form of the material is brittle fracture, and the fracture morphology exists river-like pattern, which is deconstruction fracture, and there are a lot of tearing ribs [10,19]. Combined with the previous simulation results, it can be analyzed that when the composite is squeezed by the load, stress/strain concentration is generated around the ceramic particles, and when the load reaches a critical point, the pressure is released through cracks, which in turn makes the composite fracture [17].…”
Section: Analysis Of Compressive Properties Of Configuration Compositesmentioning
confidence: 99%
“…Zhipeng Liu et al [9] studied the properties of the macrostructured composites at what pore size/pore wall ratio of the preform, and the results showed that the composite exhibited good compressive and wear resistance at this ratio when the pore size/pore wall ratio was 1.25. Dehong Lu et al [10] studied the preparation of 3D interpenetrating hierarchical Al 2 O 3 /40Cr composites by extrusion casting, and the results showed that the cracks of fracture mainly appeared in the composite region, and the 40Cr steel in the matrix region could greatly inhibit the deformation and cracking in the composite region. Li Zulai [11] et al used vacuum sintering method to prepare WC preforms and immersion casting process to obtain WC/Fe composites, and the results showed that the wear resistance of WC/Fe composites for three-body abrasive wear increased and then decreased with the increase of preformed column spacing.…”
Section: Introductionmentioning
confidence: 99%